TELUSUR SEJARAH MOTIF BATIK PADA LOMAR BADUY - Suparti, Tety; Umam, Khoirul (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
This research aims to investigate the history of batik motifs applied to the head band, or